CANÇÃO DE PIRATAS: UMA LEITURA ANFÍBIA: PIRATES SONG: AN AMPHIBIOUS READING - FERREIRA, Iasmim Santos (Travessias Interativas, 2019)
RESUMO: O presente artigo tem por objetivo fazer uma revisão da crítica literária e debruçar-se sobre a crônica “Canção de Piratas” (1894), de Machado de Assis, a fim de fazer uma leitura anfíbia desse escrito, o qual versa sobre política e arte concomitantemente. Para tanto, apresentamos uma revisão dos caminhos da crítica literária brasileira e de suas principais fontes. Alinhamo-nos ao pensamento pós-estruturalista de Silviano Santiago (2000, 2002) para melhor compreendermos a literatura brasileira e a pirataria retratada por Machado, que articula dois sentidos: os homens de Canudos e os românticos como piratas. PALAVRAS-CHAVE: Crítica. Literatura anfíbia. Machado. ABSTRACT: The present article has as objective do a review of literary critic and look over the chronicle “Canção de Piratas” (1984), by Machado de Asssis in order to make an amphibious reading into the written, which talks, concomitantly, about politics and art. Therefore, we present a review about the Brazilian literary critic ways and its main sources. We align with the post structuralism thought of Silviano Santiago (2000, 2002) to understand better the Brazilian literature and the piracy showed by Machado, which articulates two directions: the men from Canudos and the novelists as pirates. KEYWORDS: Critic. Amphibious literature. Machado.